Diagnostic signs of motor neuropathy in MR neurography: nerve lesions and muscle denervation - Schwarz, Daniel; Weiler, Markus; Pham, Mirko; Heiland, Sabine; Bendszus, Martin; Bäumer, Philipp (European radiology, 2014)
ObjectiveTo investigate the diagnostic contribution of T2-w nerve lesions and of muscle denervation in peripheral motor neuropathies by magnetic resonance neurography (MRN).MethodsFifty-one patients with peripheral motor neuropathies underwent high-resolution MRN by large coverage axial T2-w sequences of the upper arm, elbow, and forearm. Images were evaluated by two blinded readers for T2-w signal alterations of median, ulnar, and radial nerves, and for denervation in respective target muscle groups.ResultsAll 51 patients displayed nerve lesions in at least one of three nerves, and 43 out of 51 patients showed denervation in at least one target muscle group of these nerves. In 21 out of 51 patients, the number of affected nerves matched the number of affected target muscle groups. In the remaining 30 patients, T2-w lesions were encountered more frequently than target muscle group denervation. In 153 nerve-muscle pairs, 72 showed denervation, but only one had increased muscle signal without a lesion in the corresponding nerve.ConclusionsMRN-based diagnosis of peripheral motor neuropathies is more likely by visualization of peripheral nerve lesions than by denervation in corresponding target muscles. Increased muscular T2-w signal without concomitant nerve lesions should raise suspicion of an etiology other than peripheral neuropathy.Key Points• In peripheral neuropathy, T2-w nerve lesions are more frequent than muscle denervation.• Muscle denervation almost never occurs without detectable lesions in corresponding nerves.• MRN-aided diagnosis of peripheral motor neuropathy should focus primarily on nerve lesions.• Increased muscular T2-w signal intensity without concomitant nerve lesions indicates other aetiology.